2004
DOI: 10.1002/jcc.20085
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the Cr(III) ion in aqueous solution: Ab initio QM/MM molecular dynamics simulation

Abstract: Structural and dynamical properties of the Cr(III) ion in aqueous solution have been investigated using a combined ab initio quantum mechanical/molecular mechanical (QM/MM) molecular dynamics simulation. The hydration structure of Cr(III) was determined in terms of radial distribution functions, coordination numbers, and angular distributions. The QM/MM simulation gives coordination numbers of 6 and 15.4 for the first and second hydration shell, respectively. The first hydration shell is kinetically very inert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 48 publications
(55 reference statements)
6
38
1
Order By: Relevance
“…[21][22][23][24] To describe the interactions between ion and water in the system, the approximation of pairwise additivity is generally applied. [27][28][29][30][31] To include the complicated many-body effects within the hydration shell of ions, the hybrid quantum mechanical/molecular mechanical (QM/MM) methods have been introduced 32,33 and lately applied to investigate structural and dynamical properties of various ions in solutions. . .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] To describe the interactions between ion and water in the system, the approximation of pairwise additivity is generally applied. [27][28][29][30][31] To include the complicated many-body effects within the hydration shell of ions, the hybrid quantum mechanical/molecular mechanical (QM/MM) methods have been introduced 32,33 and lately applied to investigate structural and dynamical properties of various ions in solutions. . .…”
Section: Introductionmentioning
confidence: 99%
“…The force constant of the ion-O bond (171 N m −1 ) is higher than that of Al(III) (160 N m −1 ), 22 and similar to that of the trivalent transition metal ion Cr(III) (174 N m −1 ). 19 The stability of the second shell, however, is higher for Al(III) (MRT = 26.4 ps), while the MRT for the second shell of Tl(III) (12.8 ps) is still higher than that for Cr(III) (7.5 ps). This ranking of stability is not correlated with the size of the shell, containing 12, 18, and 15 ligands in the case of Al(III), Tl(III), and Cr(III), respectively.…”
Section: Resultsmentioning
confidence: 88%
“…The tilt and θ distributions of the first hydration shell indicate stronger angular distortions of the ligands coordinated to Tl(III) than for those binding to other trivalent cations such as Ti(III), 24 Cr(III), 19 and Co(III), 25 probably due to the longer ionligand distance in the case of Tl(III). For the second hydration shell, the tilt angle shows a broad peak with its maximum situated approximately at −18…”
Section: Structural Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…This is the same trend as observed in the tetrafluorouranylate ion, but the effect is smaller, keeping the hexa conformation the most stable. In an extensive QM/MM MD study, with all first shell water molecules in the QM region, Kritayakornupong et al 34 have shown that the error in a QM/MM calculation of hydration enthalpies for the Cr(III) ion is of the order of 30 kJ/mol. Assuming that a similar error bar is applicable in our calculations, we conclude that the energy difference between the hexa and hepta coordination (72.4 kJ/mol in the QM/MM model and 43.1 kJ/mol in the full QM model) is large enough to support the interpretation that hexa coordination dominates in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%